ADMINISTRATIVE ACTIVITY AND MANAGEMENT IN EDUCATION SOCIAL FACTORS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
In this article, management activities in the educational system,the role of management, goals and tasks, principles, management social factors were discussed.